2017
DOI: 10.7860/jcdr/2017/24977.9879
|View full text |Cite
|
Sign up to set email alerts
|

Occupation Hazards – Pattern, Awareness and Preventive Measures among Welders from an Unorganized Sector in India

Abstract: The period prevalence of morbidity was high among the welders surveyed. Ignorance of health hazards associated with occupation and non-usage of protective gears was reported by number of them. Therefore, health education and safety policies need to be strengthened at welding sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
2
4
1
Order By: Relevance
“…A review of literature indicates contrasting findings regarding the training of welders in low-income countries. Although our findings are consistent with those reported by Joseph et al ( 2017 ) among welders in the informal sector in India, which indicated that the majority were trained by apprenticeship, this is in contrast to the evidence generated by Alexander et al ( 2016 ), which indicated that almost all welders in India had neither any formal training nor apprenticeship.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A review of literature indicates contrasting findings regarding the training of welders in low-income countries. Although our findings are consistent with those reported by Joseph et al ( 2017 ) among welders in the informal sector in India, which indicated that the majority were trained by apprenticeship, this is in contrast to the evidence generated by Alexander et al ( 2016 ), which indicated that almost all welders in India had neither any formal training nor apprenticeship.…”
Section: Discussionsupporting
confidence: 84%
“…Welders in the small-scale metal workshops in Uganda engage in high-risk activities such as heavy lifting, cutting, polishing and joining metal parts, which predispose them to physical, chemical and ergonomic hazards (Atukunda et al, 2019 ; Itiakorit et al, 2021 ). The commonest technologies used in these workshops are electric arc and oxy-fuel gas welding which produce welding fumes that are detrimental to health (Joseph et al, 2017 ). Besides the fumes, welders in small-scale metal workshops are exposed to noise, dust, intense light, heat, electric shock, fires, vibrations from machinery, repetitive work and heavy lifting, whose risk can be exacerbated by the non-usage of personal protective equipment (PPE) and lack of administrative controls (Alexander et al, 2016 ; Atukunda et al, 2019 ; Oluwole et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study in India showed that workers that did not wear gloves had a higher number of injuries. (19) Compared to the current study, the use of this piece of PPE was higher, but the probability remained the same; namely, the occurrence of manifestations was higher for those who did not wear it. The focus is particularly on the PPE gloves because it was maintained in the analysis model with statistical significance, which allowed to link it to ocular manifestations and to demonstrate its protective efficacy.…”
Section: Discussioncontrasting
confidence: 72%
“…The multiplicity of factors, such as heat, burns, radiation (ultraviolet, visible and infrared), noise, gases, electrocution, uncomfortable postures involved in the work, the great variability in the chemical composition of welding fumes, the method used, the surrounding environment and the routes by which these harmful agents enter the body make this occupation a potential health hazard for the welder [1] [4]- [9]. Ocular morbidities, including ocular arc, photokeratitis, double vision and retinal damage related to the welding occupation are common among welders [2] [10] [11]. The limitations of this study were that clinical consultation was not made to determine the sequellar lesions of the ocular involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Welders have been identified as a high-risk group for occupational eye injuries due to their continuous exposure to ultraviolet radiation (UV) and welding projectiles [1]. Ocular morbidities, including ocular arc, photokeratosis, diplopia Occupational Diseases and Environmental Medicine and resulting retinal damage are common [2]. The use of protective eyewear during welding helps to reduce the harmful effects of UV visible and infrared radiation.…”
Section: Introductionmentioning
confidence: 99%